Comparison of moderate electric field and conventional marination methods applied to chicken breast muscles. (2nd July 2020) - Moreno, Jorge; Mphachoe, Pabala; Sáez‐Trautmann, Guido; Guerra‐Valle, María; Simpson, Ricardo; Nuñez, Helena
Abstract: This research aimed to compare the effect of the brine‐salting process when applying a moderate electric field (MEF) and during conventional treatment of chicken breast muscles. Chicken breasts were cut into cylindrical shapes, either longitudinally or cross‐section according to muscle fibers, with dimensions of 2 × 3 cm 2 . Samples were submerged in marinade solutions (salt and polyphosphate‐ PO 4 3 − ) at concentrations of 3, 5, and 7% at 4°C for 300 min of processing. The results showed that the mass transfer of chloride and polyphosphate ions was best with the 5% marinade in combination with an MEF, obtaining 0.20 Xcl + PO 4 3 − by the end of the processing time; for the conventional treatment, the 7% concentration improved the mass transfer of ions in the treated samples compared to that of the other conventionally marinated samples. In terms of the longitudinal cut, the 3% concentration combined with an MEF presented better results than those of the same concentration using the conventional method. However, the 7% and 5% concentrations using conventional treatment exhibited mass transfer values of 0.17Xcl + PO 4 3 − and 0.08Xcl + PO 4 3 −, respectively, in the final samples. Practical applications: In the meat industry, marination is a primary process. As an alternative to reduce marinating time, moderate electric fields (MEFs) may be applied in chicken breasts without affecting the product quality. Likewise, the cut of muscle fibers will influence the marination process. The utilization of an MEF at 5 V during the marinating process presented greater efficiency in chicken breast marination than a cross‐sectional cut with polyphosphate chloride solution at 7%, reaching a 120 min reduction in the process compared to conventional methods. Abstract :